Investigation of cadmium removal using tin oxide nanoflowers through process optimization, isotherms and kinetics - Gursoy, Selim; Bombom, Miray; Zaman, Buse Tugba; Turak, Fatma; Bakirdere, Sezgin; Er, Elif Ozturk (NATURE PORTFOLIO, 2025)
The present study demonstrates a treatment approach that utilizes flower-shaped tin oxide nanoparticles for the removal of cadmium from synthetic wastewater by adsorption. Tin oxide nanoparticles were synthesized using a simple and eco-friendly method and employed for the removal of cadmium ions from wastewater. The nanoflowers were successfully characterized using Fourier Transform Infrared Spectroscopy, X-Ray Diffraction Analysis, Scanning Electron Microscope and Brunauer-Emmett-Teller (BET) surface area analysis. The batch adsorption process was optimized by response surface methods to investigate the influential parameters of the adsorption process. Optimal removal efficacy was achieved at a pH value of 9.0, a mixing time of 20 min, and an adsorbent amount of 15 mg. The results indicated that the adsorbent achieved a maximum removal efficiency of 99.14 +/- 0.10% for Cd(II)ions in domestic wastewater. The adsorption equilibrium process was elucidated by Langmuir, Freundlich, Sips and Toth isotherm models using nonlinear regression. In addition, error functions such as Chi-square (X2, Average Relative Error (ARE), Root Mean Squared Error (RMSE) and HYBRID were used to test the validity of the nonlinear models. The results indicated that the Sips model, with an R2 value of 0.9894, accurately matched the experimental data and adsorption capacity of 57.12 mg g- 1 for Cd(II) was calculated respectively. The sorption kinetics were well characterized by a pseudo-second-order kinetic model. The results demonstrated that adsorption of cadmium onto the surface of SnO2 nanoparticles is influenced by both monolayer adsorption and multi-site interactions. These findings indicate that SnO2 nanoparticles are suitable for removing cadmium from aqueous solutions in batch processes.
Keywords: Adsorption isotherms; Experimental design; Heavy metal removal, domestic wastewater, nanoflowers; HEAVY-METAL IONS; ORGANIC-DYES; ADSORPTION; Science & Technology - Other Topics